Tanggung Jawab Pidana Korban Pemerkosaan Aborsi Janin Ditinjau dari Perspektif Hak Asasi Manusia - Ni Luh Putu Sri Laksemi Dharmapadmi; Anak Agung Sagung Laksmi Dewi; l Made Minggu Widyantara (Warmadewa Press, 2021)
Indonesia is a Legal State whose all aspects of citizens' lives are always rules and norms, be it sanctions or legal responsibilities that participate in growing in society. Responsibilitycan not only be imposedon the wrong-maker but the victim can shoulder this. From the statement, there are problems, namely the legal protection of victims of fetal abortion rape reviewed from a human rights perspective and criminal sanctions againstfetal abortion perpetrators based on human rights. This study aims to determine how the law of covering rape victims who perform fetal abortion. This writing uses the normative legal writing method where the writing is about principles, norms, and rules. In this writing the rape victim who decided to abort her fetus, this certainly makes the responsibility carried also by the victim who abortions her fetus caused by rape and makes the pregnancy that is not stopped that leads to abortion. Surely this is very contrary to the criminal law as well as the human rights of thefetus. Thispaper describesthat the responsibility of rape victims to the fetus abortion can be seen in terms of the human rights of a fetus and the victim himself.